GAMBARAN PERSONAL HYGIENE DAN INFEKSI SOIL-TRANSMITTED HELMINTHS PADA ANAK PANTI ASUHAN WILAYAH KOTA PADANG TAHUN 2023 - Putri, Salsa Utami; Hasmiwati, Hasmiwati; Rusjdi, Selfi Renita; Irawati, Nuzulia; Lestari, Rahmi; Burhan, Ida Rahmah (SINERGI : Jurnal Riset Ilmiah, 2025)
Orphanage children are group that is vulnerable to infections, which one is Soil-Transmitted Helminths infection. This happens because the limited number of caregivers results in a lack of monitoring of the personal hygiene conditions of their foster children. This research aims to determine the description of personal hygiene and Soil-Transmitted Helminth infections in orphanages  children in the City Padang area in 2023. This research is descriptive research conducted in several orphanages in Padang City. This research was conducted from October to December 2023 with 110 respondents. Sampling in this research used a total sampling technique. The research instrument used was a personal hygiene questionnaire sheet. Soil-Transmitted Helminths infection data was obtained from direct fecal laboratory examination results. The research results showed that 56.4% of respondents had poor levels of personal hygiene and 43.6% of respondents had good personal hygiene , and no Soil-Transmitted Helminths infections were found in children from orphanages in the Padang City area in 2023